2013
DOI: 10.1089/vbz.2012.1137
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence forBorrelia hermsiiInfection in Rodents on Federally Owned Recreational Areas in California

Abstract: Tick-borne relapsing fever (TBRF) is endemic in mountainous regions of the western United States. In California, the principal agent is the spirochete Borrelia hermsii, which is transmitted by the argasid tick Ornithodoros hermsi. Humans are at risk of TBRF when infected ticks leave an abandoned rodent nest in quest of a blood meal. Rodents are the primary vertebrate hosts for B. hermsii. Sciurid rodents were collected from 23 sites in California between August, 2006, and September, 2008, and tested for serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…), and pine squirrels ( Tamiasciurus spp.) are suitable hosts to varying degrees [ 48 , 49 , 68 , 70 , 72 , 73 , 74 ].…”
Section: Ecology Of Abrf In North Americamentioning
confidence: 99%
“…), and pine squirrels ( Tamiasciurus spp.) are suitable hosts to varying degrees [ 48 , 49 , 68 , 70 , 72 , 73 , 74 ].…”
Section: Ecology Of Abrf In North Americamentioning
confidence: 99%
“…The susceptibility experiments suggest these animals had been infected with GGII spirochetes however, our serological tests do not discriminate between the genomic groups of B. hermsii that caused the infection. In the only other large serological study investigating the presence of anti- B. hermsii antibodies in wild rodents, only 2 of 133 (1.5 %) deer mice tested in California were seropositive [29]. Yet, during a site investigation on Mt.…”
Section: Discussionmentioning
confidence: 99%
“…Yellow-pine chipmunks were far less abundant and rarely captured, yet two of only five individuals we tested were seropositive. This species extends south into the northeastern mountainous half of California [49], where two serological surveys found 36 % (4 of 11) and 47.2 % (34 of 72) of these animals seropositive with anti- B. hermsii antibodies [28, 29]. Subsequent to our field study at Flathead Lake, we found seropositive yellow-pine and red-tailed chipmunks in the Bitterroot Valley to the south in western Montana, and one yellow-pine chipmunk was infected with a GGI A B. hermsii [31].…”
Section: Discussionmentioning
confidence: 99%
“…Unfed larvae, which feed on white-footed mice too but are not infected transovarially [ 88 ], and adult ticks that feed on much larger mammals like deer [ 47 ], play no direct role in the chain of infection [ 89 ]. In striking contrast, every active stage of O. hermsi has the potential to transmit B. hermsii when they feed on their hosts, primarily squirrels and chipmunks ( Tamiasciurus spp and Tamias spp) [ 90 , 91 ]. Larvae may become infected transovarially [ 92 , 93 ], although the frequency of this event needs further study.…”
Section: Discussionmentioning
confidence: 99%